IMPLEMENTASI EKONOMI ISLAM DALAM AKAD PNPM MANDIRI KECAMATAN PELEPAT ILIR KABUPATEN BUNGO - Geby Saputri; M. Taufik Ridho; Yunus M. (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This study aims to analyze the contract used and how the mechanism is used in the PNPM Mandiri government activity program in an effort to empower the poor who need business capital that is designated especially for women, so that women have activities that can help their household needs. This research is a qualitative research or often referred to as naturalistic research because the research is carried out in natural conditions. The subjects of this study were members of PNPM Mandiri employees and members of the target community who were given business loans in Pelepat Ilir District, Bungo Regency. Data obtained through observation, interviews, and documentation. The results showed that the contract used in the PNPM Mandiri government program activities in Pelepat Ilir District, Bungo Regency in an effort to empower the poor, specifically for women, was the 'ariyah (loan) contract. The loan agreement is considered to be able to provide convenience for women to get additional family economic income even if only at home. The business credit assistance can be submitted by submitting a written application and including how much capital is needed to develop a business or plant maintenance that will be carried out by members of the target community. Thus, the results of research at PNPM Mandiri, Pelepat Ilir District, Bungo Regency have been well achieved.